Integrasi Konsep Energi Potensial dan Potensi Diri Santri dalam Pendidikan Pesantren - Ash-Shiddieqy, Muhammad Hasbi (Universitas Garut, 2025)
This study aims to examine the relationship between the concept of potential energy in physics and the self-potential of santri (Islamic boarding school students) within the context of pesantren education. Using a descriptive qualitative method with a literature review approach, this research analyzes textbooks on physics, nationally accredited SINTA journals (2021–2025), and Islamic educational references. This approach was chosen because it is able to explain phenomena in depth through analysis of various relevant written sources. The findings indicate that potential energy defined as stored energy that can be actualized under certain conditions serves as an appropriate analogy to describe the latent potential of santri that needs to be nurtured through character education, spiritual strengthening, and technological integration. In the Society 5.0 era, pesantren education must not only preserve tradition but also adapt to advancements in science and technology. This study recommends developing an integrative curriculum based on science and Islamic values to holistically support santri's self-potential development.